Pengaruh Good Corporate Governance dan Transfer Pricing terhadap Penghindaran Pajak - Tati Rosyati; Rhiantha Puri Dewi Rengganis; Fernanda Sefy Atasya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to examine the effect of Good Corporate Governance measured using Independent Commissioners and Audit Committees as well as Transfer Pricing variables on Tax Avoidance. This type of research uses quantitative methods using secondary data. The population in this study is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange in 2020 - 2024. The sampling method used is purposive sampling. The number of samples in this study was 27 companies for 5 years so the total research data was 135. Hypothesis testing used panel data regression tests with the help of the Eviews version 12 program. Based on the results of the F test, it can be seen that Good Corporate Governance measured using Independent Commissioners and Audit Committees and Transfer Pricing variables have a significant effect on tax avoidance with an F-statistic value of 0.000000 <0.05. Based on the results of the t-test, it can be seen that the Independent Commissioner variable has a significant effect on tax avoidance with a probability value of 0.0004 < 0.05, the Audit Committee variable has a significant effect on tax avoidance with a probability of 0.0001 < 0.05. The Transfer Pricing variable does not have a significant effect on tax avoidance with a probability of 0.2152 > 0.05